Perbaikan Proses Bisnis Layanan Perkreditan Menggunakan Metode Business Process Improvement (BPI) Dengan Metode Failure Mode and Effect Analysis (FMEA) Pada PT.BPR Bina Reksa Karyaartha Pare - Inka Setya Anggraini; Yusi Tyroni Mursityo; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
BPR Bina Reksa Karyaartha is a company engaged in several financial services, such as credit services. In the credit service there are business functions, i.e providing credit to customers, serving credit payments, and credit reporting. Problems that can interfere the performance of ongoing business processes in this case are errors in filling the application form, Account Officers have difficulty contacting customers to determine the credit agreement schedule, and errors entering customer data, credit data and collateral data on the PGBS application. In addition, customers are late paying, collectors find it difficult to do billing with customers, and errors in making SLIK reports. The stage of this research is to identify business processes by conducting interviews and observations, then modeling business processes using Business Process Models and Notation (BPMN) with the Bizagi Modeler application, conducting analysis and evaluation using the Failure Mode and Effect Analysis (FMEA) method to find out the highest potential problem. Furthermore, improvements to business process recommendations are made using the Business Process Improvement (BPI) method with the help of streamlining tools and simulation of current business processes (as is) and recommendations (to be) on all business processes. An increase in time analysis reached 9.24%. If a business process recommendation is implemented, it will minimize some problems mentioned above also improve the quality of employee performance and collaboration with customers.